Factors That Influence Nurse Compliance in Using Personal Protective Equipment at Mufid Sigli General Hospital - Istikbal, Muhammad; Nuraini; Mu’alim, Azhar (International Journal on ObGyn and Health Sciences, 2023)
The hospital is a health facility unit for the community which is inseparable from the occurrence of work accidents, especially for health workers, one of the reasons is that nurses who use PPE are not in accordance with the Hospital Standard Operating Procedures (SOP). There are still many health workers who are not compliant with using personal protective equipment. This study aims to analyze the factors that influence nurse compliance in using Personal Protective Equipment at Mufid Sigli Hospital. This research is a quantitative study with a cross-sectional study design conducted at Mufid Sigli Hospital. The sample in the study was determined by the total sample technical formula, so that there were 65 nurses in the sample. The results showed that there was an influence of nurses' attitudes on nurses' adherence in using PPE, hospital regulations on nurses' compliance in using PPE, convenience for nurses' compliance in using PPE, supervision of nurses' compliance in using PPE, availability of facilities on nurse compliance in using PPE in Mufid Sigli Hospital. It is recommended that nurses should be able to use Personal Protective Equipment to minimize the occurrence of work accidents, it is suggested to the hospital to increase supervision and impose sanctions for health workers who do not use personal protective equipment, complete personal protective equipment and ensure that PPE can always be used effectively and efficiently